The U-Curve of Happiness Revisited: Correlations and Differences in Life Satisfaction Over the Span of Life—An Empirical Evaluation Based on Data From 1,597 Individuals Aged 12–94 in Germany - Karwetzky, Christopher; Michaelsen, Maren M.; Werdecker, Lena; Esch, Tobias (Frontiers in Psychology, 2022)
Background: Subjective well-being (SWB) is a research topic of growing interest for different disciplines. Based on a cross-sectional survey with 1,597 participants aged 12 to 94, this study investigated life satisfaction and momentary happiness, two important dimensions of SWB. We examined their relationship, shape, and correlates across individuals of different ages and interpreted the results in the light of a neurobiological model of motivation systems. Methods: Statistical analyses were performed using multiple linear regression. First, we examined how life satisfaction is associated with selected socio-demographic variables across four age groups. Second, we analyzed the association between life satisfaction and age, and lastly, we examined the extent to which happiness is a prerequisite for life satisfaction in each age group. Results: Our analyses show that life satisfaction correlates negatively with poor health and financial worries, and positively with partnership, grandchildren, and religiosity. However, the inverse relationship with poor health is stronger in younger than in older individuals, while the inverse association with financial worries is strongest in late midlife (50 to 69 years). We identified gender-specific differences concerning the relationship between life satisfaction and age, with males displaying a U-shape trend with its lowest point between the ages of 30 and 49, whereas females’ life satisfaction increases stepwise with age. Although momentary happiness correlates strongly with life satisfaction, this relationship decreases with age. Conclusions: The results suggest that individuals adjust, or even grow beyond, their perceptions of a “good life” over time. Neurobiological processes of adaptation and personal growth could play an important role in these developments.